The role of PET/CT in the diagnosis of metastatic uveal melanoma - S. V. Saakyan; K. V. Avakyan; A. G. Amiryan; I. P. Aslanidi; O. V. Mukhortova (Российский офтальмологический журнал, 2018)
Uveal melanoma (UM) is an aggressive tumor with a high risk of death due to metastatic disease development. Therefore, it is an important task to find new methods of early diagnosis of metastases in UM patients. Purpose: to assess the method of positron emission tomography combined with computer tomography (PET / CT) used for metastatic UM detection as compare to routine examination techniques. Materials and Methods. The study involved 50 UM patients (18 males and 32 females) aged 26 to 78 (average age 52 ± 13). Of these, 27 patients were examined before treatment start and 23 patients underwent examination 3 to 166 months after being diagnosed with UM (the median was 26 ± 10 months). Metastatic disease screening included liver enzymes level evaluation, ultrasound imaging of the abdominal cavity, chest X-ray, and PET/CT). Results. The liver enzyme level was elevated in one patient with disseminated lesion. In one case, chest X-ray showed fibro-focal changes in the lungs (after previous tuberculosis) were detected. Ultrasound imaging of the abdominal cavity revealed focal liver damages in 13 patients, of which 11 patients had liver formations that were regarded as cysts or hemangiomas and in one case a secondary character of damage was suspected (later, a cyst was diagnosed). Only in one remaining case, multiple focal lesions in the liver (metastases) were revealed reliably. PET/CT imaging showed UM metastases in 6 patients (2 primary and 4 recurrent patients): one case showed multiple metastases to the liver, lungs, bones, peritoneum, retroperitoneal space, intestinal loops) and 5 cases were diagnosed with metastases in the liver. The metastasizing periods were 21 to 160 months (median 74 ± 58 months) from the moment of UM diagnosis. One female patient who was diagnosed with primary uveal melanoma revealed, in addition to a metastatic lesion of the liver, a lesion focus in the sigmoid colon (adenocarcinoma, a synchronous cancer). In 14 patients (22 %), PET/CT revealed small focal changes (less than 5 mm) of uncertain etiology in the lungs. PET/CT also detected concomitant diseases (inflammatory, benign, degenerative dystrophic etc.). Conclusions. PET/CTis the most informative examination method enabling the detection of malignant focal processes and accompanying pathologies which is crucial for choosing the optimal treatment of UM patients and may be able to increase their life expectancy // Russian ophthalmological journal. 2017; 10 (2): 54-61. (in Russian). doi: 10.21516/2072-0076-2017-10-2-54-61.